THE INFLUENCE OF PROMOTIONS, CUSTOMER SATISFACTION AND SERVICE QUALITY ON PURCHASE DECISIONS AT ALFAMART BIREUEN DISTRICT - Anhar Mubarak; Muchsin; T. Edyansyah; Teuku Zulkarnaen (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research aims to determine the effect of promotions on purchasing decisions among Alfamart consumers in Bireuen. The influence of customer satisfaction on purchasing decisions for Alfamart consumers in Bireuen. The influence of service quality on purchasing decisions for Alfamart consumers in Bireuen and the influence of promotions, customer satisfaction and service quality on purchasing decisions for Alfamart consumers in Bireuen. The sample that will be used in this research is 100 consumers. The research method in this thesis uses quantitative methods with a descriptive approach. The data analysis tool used is multiple regression. The research results show that Promotion does not have a positive and significant effect on Purchasing Decisions at Alfamart Bireuen, Customer Satisfaction has a positive and significant effect on Purchasing Decisions at Alfamart Bireuen. Service Quality has a positive and significant effect on Purchasing Decisions at Alfamart Bireuen. Meanwhile, the results of simultaneous testing showed that the Promotion Variables (X1), Customer Satisfaction (X2) and Service Quality (X3) had a significant effect on Purchasing Decisions (Y) at Alfamart Bireuen